Risk‐stratification management of febrile neutropenia in pediatric hematology‐oncology patients: Results of a French nationwide survey. Issue 12 (28th August 2016) - Delebarre, Mathilde; Tiphaine, Aude; Martinot, Alain; Dubos, François
Abstract: Background: In 2012, new international guidelines for children with chemotherapy‐induced febrile neutropenia (FN) were issued, recommending reduced‐intensity management strategy based on stratification of infectious risks. Some studies have highlighted practice disparities in different countries and within the same country. Our aim was to assess the current management strategies for the treatment of chemotherapy‐induced FN in children in France. Procedure: This survey of all French pediatric oncology‐hematology reference centers ( n = 30) in late 2012 and early 2013 sent a standardized questionnaire to each center inquiring about their definition of an FN episode, its initial empiric treatment and ongoing management, use of management stratified by risk, and any criteria used for the risk assessment. Each center's management protocol was also analyzed. Results: All French reference centers participated in this survey, completing 88% of the questionnaire items. Definitions of both fever and neutropenia varied between centers. Ten centers used a risk‐stratification strategy for initial management. In all, 42 probabilistic first‐line antibiotic treatments were identified. After 48 hr of apyrexia, 17 units applied different forms of step‐down therapy. Conclusions: Most French centers already offered some form of reduced‐intensity or step‐down therapy, although they differed substantially in their management of FN episodes. Risk stratification with validated tools is essential to facilitate the implementation of the international recommendations, which would ultimately help to standardize practices in France.